(untitled) (Intent Research Scientific Journal, 2023)
The article examines the theoretical foundations of public procurement, research conducted by foreign and domestic scholars in this area, and develops independent authorial approaches. Also, the methodological aspects and bases of public procurement are analyzed and scientific conclusions are formed.